2013
DOI: 10.1002/pip.2375
|View full text |Cite
|
Sign up to set email alerts
|

Influences of silicon nanowire morphology on its electro‐optical properties and applications for hybrid solar cells

Abstract: In this paper, we investigate the morphology, optical, and electrical properties of silicon nanowire (SiNW) arrays and their applications on inorganic/organic hybrid solar cells. The SiNW arrays are obtained by two kinds of metal-assisted chemical etching (MacEtch) processes. One is depositing assisted metal, for example, Ag, by an electron gun evaporator before etching (BE). The other is depositing assisted Ag during the etching (DE) process. The results reveal that BE method MacEtch can produce more uniform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 38 publications
(98 reference statements)
0
18
0
Order By: Relevance
“…Obviously, the reflectance is greatly suppressed through the entire spectra compared with that of the pyramid-textured surface, and the anti-reflection performance is even better for longer SiNWs. Actually, the reflectance in short wavelength range 300-600 nm shows much more significant improvement than that in long wavelength 900-1100 nm, which can be attributed to the fact that the sizes of the SiNWs are comparable with the short wavelengths [25]. Next, we turn to illustrate the anti-reflection effect of the Al 2 O 3 -coated Si N/M-Strus through the reflectance spectra of series D with different ALD cycles as shown in Figure 2(c).…”
Section: Anti-reflection Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, the reflectance is greatly suppressed through the entire spectra compared with that of the pyramid-textured surface, and the anti-reflection performance is even better for longer SiNWs. Actually, the reflectance in short wavelength range 300-600 nm shows much more significant improvement than that in long wavelength 900-1100 nm, which can be attributed to the fact that the sizes of the SiNWs are comparable with the short wavelengths [25]. Next, we turn to illustrate the anti-reflection effect of the Al 2 O 3 -coated Si N/M-Strus through the reflectance spectra of series D with different ALD cycles as shown in Figure 2(c).…”
Section: Anti-reflection Performancementioning
confidence: 99%
“…Unfortunately, despite the excellent optical advantages, the SiNWsbased solar cells show yet unsatisfied energy conversion efficiencies (η) because of the serious surface recombination arising from the concomitant high surface-volume ration. Many research groups have carried out many beneficial tries to minimize the optical and electrical losses and have indeed made great progresses in the performance of SiNWs-based solar cells [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Oh et al [26] have reported an 18.2% efficient nanostructure black Si solar cell through controlling the front surface area and Auger recombination.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, Shiu et al form vertical silicon nanowire (SiNW) arrays on Si wafer to decrease the reflectance and increase the absorptance by high light-trapping effect of NW structures [7]. To date, the SiNWI poly(3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS) hybrid solar cells reach the high efficiency of � 10% [8]. However, this efficiency is still not competitive with inorganic Si solar cells [9].…”
Section: Introductionmentioning
confidence: 98%
“…However, the optical advantage of Si nanostructures has not been facile to be fully converted into the η-gain of solar cells [4][5][6][7][8][9][10][11][12][13][14][15], which is mainly ascribed to the poor electrical properties, i.e., high recombination on the surface and in the bulk of Si nanostructures. Over the past several years, substantial progresses in improvement of the electric performance have been made by carrying out various process methods such as the surface passivation [16][17][18][19][20], properly increasing sheet resistance [21,22] and optimization of morphology of mc-Si nanostructures [11,13,14,19]. Using the optimized textured structure, Zhong et al, [23] and Xiao et al, [24] have reported ηs of 15.99% and 17.46% for mc-Si nanostructures based solar cells with the standard solar wafer size of 156 Â 156 mm 2 through reactive ion etching (RIE), respectively.…”
Section: Introductionmentioning
confidence: 99%